Enantioselective Synthesis, Enantiomeric Separations and Chiral Recognition (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This book includes both fundamental studies and applications in a multidisciplinary research field involving a high diversity of chiral compounds, including commercial substances with industrial applications, pharmaceuticals, and new chiral compounds with promising biological activities. Recent developments and innovative approaches to producing enantiomerically pure compounds of industrial and research interest are included. Enantiomeric separation in both the analytical and preparative scale, determination of the enantiomeric purity, insights into enantioselective synthesis and many different aspects of chiral recognition, including chiral sensors, recognition in biological systems, and in analytical methods, are presented. Original research and review articles show the broad scope of chirality in diverse analytical fields and the connection to enantioselective synthesis and biological activities.